Selection of nitrification and denitrification bacteria with its application in culture medium of Pacific white shrimp (Litopenaeus vannamei) - . Widanarni; Sugiyo Hadi Pranoto; . Sukenda (Jurnal Akuakultur Indonesia)
The aim of this study was to obtain nitrification and denitrification bacteria and tested its activity in reducing the ammonia, nitrite and nitrate compounds in culture medium of Pacific white shrimp Litopenaeusvannamei. The research was conducted through several steps: 1) Isolation of nitrification and denitrification bacteria from ponds and mangrove areas, 2) Selection of nitrification and denitrification bacteria  in vitro, and 3) test of the nitrication and denitrification bacteria activities in culture medium of white shrimp. A total of 38 isolates of nitrification bacteria and 7 isolates of denitrification bacteria were successfully isolated from ponds and mangrove areas in the region of South Lampung and Subang, West Java. Of the total isolates were then selected in vitro based on its ability to reduce the compounds of ammonia, nitrite and nitrate and selected each 2 of the best isolates. Two select nitrification bacteria isolates, namely S11 and S12 each can oxidize ammonia at 78.25% and 80.54%, whereas two select denitrification bacteria isolates namely DS7 and DS3 each can reduce nitrate amounted to 85.41%, and 56, 49%. The test results of nitrification and denitrification bacteria activities in culture medium of white shrimp showed that S12-DS7 treatments gave the best result, with ammonia concentrations between  0.007 - 0.13 mg / l, nitrite of 0.04 -2.34 mg / l, nitrate of 1 0.33 - 3, 29 mg / l, shrimp growth rate of 2.1%, and survival rate of 90%.